PERANCANGAN DAN PREDIKSI PERFORMANCE SEBUAH ALAT KONDENSOR INSTALASI PROSES PEMBUATAN ES BALOK - Darmansyah .; Chandrasa Soekardi (INTEKNA informasi teknik dan niaga, 2012)
The energy consumption of a compression refrigeration system depends the ability of the condenser to release heat. Improved condenser design can make a significant contribu-tion to increase the heat removal in the condenser that in turn reduces the energy con-sumption. This paper presents, firstly the optimization design of a condenser with the objective to estimate the minimum dimension required for a given heat duty, and se-condly the prediction of the condenser performance when it is first placed in service. Vari-ous design variables such as tube diameter, pitch ratio, tube layout, and fouling factor are considered. Simultance optimization of these variables was tried and 9 design configu-rations have been experimented. The effect of the design variables and its constraints on the number of tubes required for the condenser are discussed. The results showed that the design conditions that give the minimum number of tube of 187 will be at tube diame-ter 1.5 inch, tube layout 30o, pitch ratio 1.25, and excess area 1.25.  The results of the performance calculations showed that when the condenser is first placed in service its performance is beyond the design conditions. The condenser performance will attain its design conditions when the fouling factor approachs the value that was selected at the design stage.